KONSEPTUALISASI PERAN TEKNOLOGI INFORMASI DALAM PRAKTIK AUDIT UNTUK MEMBANTU PENGUNGKAPAN FRAUD DI INDONESIA - Suryani, Indrika Dwi Rahma; Kurniawati, Elia; Wulan, Gracia Angelina Nawang; Dinniah, Hikmah Cahya (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2021)
So many cases of fraud have accured in Indonesia as well as the world today has entered the digital era. This study aims to determine with the development of information technology their role in audit practice in detecting fraud in Indonesia. The method used in this research is a systematic literature review using secondary data derived from literature and online media. The results of this study indicate that currently many techniques are used in detecting fraud by employing information technology such as general audit software, computer forensics, DFM (Digital Forensic Model) and whistleblowing systems that are now shifthing to digitization.